Die Habermas-Foucault-Debatte neu gelesen: Missverständnis, Diffamierung oder Abgrenzung gegen Rechts? - Bühl, Achim (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
The work of Foucault is reconstructed referring to the discussion between Habermas and Foucault. The controversy doesn’t found on a misunderstanding - as Bourdieu assumes - but on a fundamental opposition between the type of a universal intellectual and the intellectual as a destroyer of the normative principle of universal rationalism and of common truth, The quality of Foucault as a theorist of modernity is based upon his reply to the question for the inherent potential of barbarism in modern society. With the category of bio-power Foucault gives us efficient answers to sociological problems concerning the dichotomies between the micro and macro sphere, A productive debate between the two theorists of modernity failed because of the defamation Foucaults as a "young conservative" on the part of Habermas, The characterization as a "pre fascistic thinker" is a scandal, which caused a remaining damage in regard to the reception of Foucault.